2009
DOI: 10.1108/13598540910980279
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance programs and access to international markets: the case of horticultural processors in Vietnam

Abstract: Purpose-The purpose of this paper is to seek to show how the implementation of different quality assurance programs (QAPs) affects international market access for horticultural processing firms in developing countries. Design/methodology/approach-A representative survey of 50 registered firms processing horticultural produce in Vietnam was conducted. Logistic regression models are used to analyze the effects of QAPs and other firm level factors on participation in different export supply chains. Findings-QAPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It is evident from the literature, that partnerships are important when managing the business of making chocolate. Consequently, there have been many developments towards partnerships and certification for enhancing both quality (Mergenthaler et al , 2009) and sustainability (Hamprecht et al , 2005). The most relevant ones identified in our research are the WCF, the ICI (2013), ISEAL Alliance (2013) and Fairtrade Certifications (Fairtrade, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It is evident from the literature, that partnerships are important when managing the business of making chocolate. Consequently, there have been many developments towards partnerships and certification for enhancing both quality (Mergenthaler et al , 2009) and sustainability (Hamprecht et al , 2005). The most relevant ones identified in our research are the WCF, the ICI (2013), ISEAL Alliance (2013) and Fairtrade Certifications (Fairtrade, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Henson and Reardon (2005) discussed about various quality standards both in industrialized and developing country context. Mergenthaler et al (2009) showed that how the implementation of different quality assurance programs affects international market.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It can clearly be seen that relationship management is an important activity within food logistics, because it was studied in 54 of 104 papers. One reason for this number Downloaded by [University of West Florida] at 14:29 02 January 2015 Zaharieva, Gorton, and Lingard (2003), Ahtonen and Virolainen (2009), Acharya, Kagan, andManfredo (2009), Hamprecht et al (2005), Cox, Chicksand, and Yang (2007), Whipple, Voss, and Closs (2009), Mergenthaler, Weinberger, and Qaim (2009), Dzever, Merdji, and Saives (2001, Ryder and Fearne (2003), Voss et al (2009), andTatsis et al (2006) Production 6 Van Donk and Van Dam (1996), Nakhla (1995), Van Wezel, Van Donk, and Gaalman (2006), Oke (2005), French and LaForge (2006), and Du et al (2009) Distribution is that SCMIJ, which persistently focuses on relationship management, contributed 46 papers to the study of relationship management. However, given the scope of the journals, very few papers focus on procurement issues.…”
Section: Descriptive Analysismentioning
confidence: 95%
“…Whipple, Voss, and Closs (2009) and Voss et al (2009) study how food producers go about securing quality and traceability from their suppliers and how they determine what trade-offs they are prepared to take in order to improve this. For example, the UK beef industry has several sourcing strategies (Cox, Chicksand, and Yang (2007), and horticultural processing firms can improve their access to international export markets by implementing a quality system (Mergenthaler, Weinberger, and Qaim 2009). Two more papers study procurement processes and how these can be improved through redesign or through the implementation of e-procurement (Tatsis et al 2006).…”
Section: Single Actorsmentioning
confidence: 98%